Doing Good Online: The Changing Relationships Between Motivations, Activity, and Retention Among Online Volunteers. (October 2018) - Cox, Joe; Oh, Eun Young; Simmons, Brooke; Graham, Gary; Greenhill, Anita; Lintott, Chris; Masters, Karen; Woodcock, Jamie
Advances in Internet technology are making it possible for individuals to volunteer online and participate in research-based activities of nonprofit organizations. Using survey data from a representative sample of such contributors, this study investigates their motivations to volunteer for five online volunteering projects using the Volunteer Functions Inventory. We explore relationships between these six categories of motivation and actual recorded measures of both volunteer activity and retention. We also use quantile regression analysis to investigate the extent to which these motivations change at different stages in the volunteer process. Our results show that volunteers' activity and retention tend to associate significantly and positively with the motivations of understanding and values, as well as significantly and negatively with the social and career motivations. We also find the importance of motivations changes significantly across the stages of volunteer engagement. In some cases, especially the understanding motivation, the changes observed for activity and retention are markedly different.